Analysis and Synthesis of Double Negative Dielectric Media Rectenna Systems for Ambient Microwave Energy Harvesting - Apostolia Karampatea; Katherine Siakavara (International Journal of Antennas and Propagation)
The concept of harvesting the ambient electromagnetic radiation energy, coming from public telecommunication wireless networks, has been recently subject of extensive research. Techniques proposed for this target use mainly antennas, as the grade gathering the radiation power. In this work, a method introducing the usage of specific dielectric structures with artificially negative electric permittivity and magnetic permeability (double negative media or DNG) in combination with wire dipole antenna sensors is proposed as an RF harvesting system. Theoretical study of the synthesized DNG medium’s performance and the distribution of the electromagnetic field in its interior is made, with the intention of finding the areas of maximum electric field intensity at which the antenna sensors would be positioned for maximum power scavenging. The received numerical results show that the synthesized schemes are capable of enhancing the energy gathering ability. Compared to the same antenna sensors positioned in free space, they ensure higher input voltage to the rectifier and also an increase of the available power about 10 dB. Moreover, they exhibit this performance for every direction of arrival of the incoming waves. The hybrid schemes DNG dipole antenna were designed for the Universal Mobile Telecommunication System (UMTS) frequency band, but the method is general and would be applied to any other frequency band and also with other antenna types.